Bipolar Disorder. - Goodwin, Guy (Fast facts., 2010)
Fast Facts: Bipolar Disorder is a highly accessible synopsis of current understanding of, and strategies, for bipolar disorder. Written by two experts, this book describes the diagnosis, etiology and short- and long-term treatment strategies.